(untitled) (Research, Society and Development, 2020)
Hormone replacement therapy is used as the most effective treatment currently available for menopause, in which buses or female hormone balance levels cease after the onset of menopause, which is a biological period of female life with a negative impact on menopause . development of estrogen and progesterone. Therefore, this study aims to assess controversies about the benefits and losses caused by hormone replacement therapy in menopausal women. This study consists of a qualitative and quantitative review of the literature, in which we seek to demonstrate the benefits and losses exerted by replacement therapy in women without air conditioning, through articles selected according to the main databases, such as Pubmed, Ciência Direct , BVS, LILACS of the last six years and according to the descriptors registered and indexed in the Decs and according to the inclusion requirements of the study. The study showed a great balance of benefits and losses in the use of replacement therapy, but with an emphasis on the benefits, there was also a great interaction of these hormonal effects with different, beneficial and harmful systems, showing that the hormones affected by several of them do not work without the female system; Therefore, if used rationally, damage can be minimized. but, with an emphasis on benefits, there was also a great interaction of these hormonal effects with different systems, whether beneficial or harmful, showing that the hormones affected by several do not work without a female system; Therefore, if used rationally, damage can be minimized. but, with an emphasis on benefits, there was also a great interaction of these hormonal effects with different systems, whether beneficial or harmful, showing that the hormones affected by several do not work without a female system; Therefore, if used rationally, damage can be minimized